Condition Monitoring of Aircraft Composite Structure using Infrared Thermography - MOHD RAZAL, MUHAMMAD HAZIQ BIN; Ir. Ts. MAZNAN BIN ISMON, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This thesis deals with composite aircraft structure condition monitoring based on infrared thermography and FLIR technologies. The primary objectives are to identify irregularities in airplane structure and secondly, by closely analyzing the time-delayed infrared images captured during FLIR tests for a maximum inspection period. The scope of the study comprises applying a model for an aircraft belonging to University Tun Hussein Onn Malaysia (UTHM) recommended in a hangar that forms an appropriate case study. This research attempts to assess the effectiveness of infrared thermography for monitoring composite structure conditions based on certain distinctive features derived from UTHM aircraft. The study utilizes advanced equipment like the FLIR T640 and Flir tools for accuracy. These instruments are used for high-resolution infrared images, which further analysis helps determine the structural health of composite components. Time comparison will help determine the best time for inspections, revealing the advantages and disadvantages of active and passive inspection methods throughout 24 hours. The ability to enlighten the efficacy of infrared thermography in this context will contribute significantly towards helping boost improvements for aircraft maintenance strategies, thus upholding the safety and reliability of modern aviation systems.